2003
DOI: 10.1007/s00436-003-0934-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses in mice infected with Clonorchis sinensis

Abstract: FVB and BALB/c mice show different morbidity, development of Clonorchis sinensis, and pathological changes following C. sinensis infection. FVB mice are susceptible and BALB/c mice are relatively more resistant to C. sinensis infection. To investigate the relationship between cytokine reaction and susceptibility to C. sinensis infection in FVB and BALB/c mice, we described both the patterns and kinetics of Th1 cytokines and Th2 cytokines in spleen cell culture. Interleukin (IL)-4 and IL-10 cytokine production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 30 publications
8
43
0
2
Order By: Relevance
“…In addition, rabbits and rats are not appropriate hosts for this purpose because they have no gallbladders. Therefore, mice are substitutable for hamsters to study host-parasite interaction of C. sinensis since they have gallbladders, and their antibodies or other reagents are commercially available [19][20][21]. Importantly, C3H/HeN together with C3H/HeJ mice (a deficient function of TLR4) will provide contrastive data for further exploring the role of TLR4 in C. sinensis infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rabbits and rats are not appropriate hosts for this purpose because they have no gallbladders. Therefore, mice are substitutable for hamsters to study host-parasite interaction of C. sinensis since they have gallbladders, and their antibodies or other reagents are commercially available [19][20][21]. Importantly, C3H/HeN together with C3H/HeJ mice (a deficient function of TLR4) will provide contrastive data for further exploring the role of TLR4 in C. sinensis infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factors and molecular mechanisms underlying polarization of the immune response are largely unknown [19][20][21]. Recent studies have shown that the expression of TLR2 and TLR4 is upregulated in other helminth infections, such as Fasciola spp., Schistosoma spp., Taenia spp., and Brugiamalayi, suggesting that TLRs might play an important role during helminth infections [22][23][24][25][26][27] …”
Section: Introductionmentioning
confidence: 99%
“…The immunology of FVB/NJ mice is far less studied, although they are considered Th2 biased (30). FVB/NJ mice are susceptible to mycobacterial infection (31) but are also clearly immunologically distinct in many ways from BALB/cJ mice (23). Therefore, lactational transfer of passive cellular immunity and Th1-based maternal educational immunity from a C57BL/6J dam to BALB/cJ and FVB/NJ foster pups has different challenges from the syngeneic/congenic pairings.…”
Section: Discussionmentioning
confidence: 99%
“…After systemic or pulmonary BCG infection, a significantly lower Th1 response in BALB/cJ mice was also evident compared with C57BL/6J mice (19,21,22). In some reports, FVB/NJ (H-2K q ) mice have been described as even more Th2-biased than BALB/cJ mice (23), although the immunology of FVB/NJ mice has been relatively poorly investigated.…”
mentioning
confidence: 99%
“…В ранних исследованиях исключалась возможность моделирования O. felineusиндуцированного описторхоза у мышей ин бредной линии C57BL/6 (Зеленцов, 1974). В то же время, как подчеркивают некоторые авторы (Choi et al, 2003), это создает определенные сложности для исследований, поскольку основные современные молекулярные и био химические разработки в научных лабораториях подра зумевают использование, прежде всего, крыс и мышей. Как сообщает компания Labome (2012), проанализиро вавшая около 10 000 публикаций за период 2008-2011 гг., мыши являются предпочтительными лабораторными животными для исследований, а инбредная линия мышей C57BL / 6, геном которых был полностью секвенирован в 2005 г., на втором месте после генома человека, самая используемая линия для создания физиологических или патологических моделей в экспериментах in vivo.…”
Section: Hereditary Features Of Physiological Functionsunclassified